Okužbe umetnih sklepov - Militarov, Anže (Medicinski razgledi, 2006)
Demographic trends and advances in surgery have led to an increase in treatment of prosthetic joints in the developed world. Orthopedic replacement surgery has revolutionized medicine with various joint implants and has thus provided millions of people with mobility and a life free of pain. Prosthetic joint infections are relatively rare, however, they are the most severe complication and account for a substantial proportion of health care expenditures. Pathogens causing the infection of implants typically grow in biofilms that protect the microorganisms against the host's immune defences and antibiotics. It is therefore imperative to promptly and accurately recognise, diagnose and treat prosthetic joint infections. Despite the rapid development of various diagnostic techniques such as diagnostic imaging, microbiological, biomolecular diagnostics and others, modern diagnostics for prosthetic joint infection are not always straightforward and current laboratory methods still depend on isolation of a pathogen by culture from synovial fluid or periprosthetic tissue. Successful treatment of prosthetic joint infections requires antimicrobial therapy in combination with surgical treatment including necrectomy, drainage, local antibiotic treatment or even removal of the prosthesis and re-implantation. Combined, antimicrobial and surgical treatment regimens are predominantly effective.
Keywords: Biofilmi; Prosthesis-Related Infections; Proteza-povezane infekcije; Joint Prosthesis; Sklepna proteza; Biofilms; diagnostika; proteze; sklepi; infekcije; therapy; zdravljenje